The Employer Potential of MOOCs: A Mixed-Methods Study of Human Resource Professionals’ Thinking on MOOCs - Radford, Alexandria Walton; Robles, Jessica; Cataylo, Stacey; Horn, Laura; Thornton, Jessica; Whitfield, Keith (International Review of Research in Open and Distributed Learning, 2014)
While press coverage of MOOCs (massive open online courses) has been considerable and major MOOC providers are beginning to realize that employers may be a market for their courses, research on employers’ receptivity to using MOOCs is scarce. To help fill this gap, the Finding and Developing Talent study surveyed 103 employers and interviewed a subset of 20 about their awareness of MOOCs and their receptivity to using MOOCs in recruiting, hiring, and professional development. Results showed that though awareness of MOOCs was relatively low (31% of the surveyed employers had heard of MOOCs), once they understood what they were, the employers perceived MOOCs positively in hiring decisions, viewing them mainly as indicating employees’ personal attributes like motivation and a desire to learn. A majority of employers (59%) were also receptive to using MOOCs for recruiting purposes—especially for staff with technical skills in high demand. Yet an even higher percentage (83%) were using, considering using, or could see their organization using MOOCs for professional development. Interviews with employers suggested that obtaining evidence about the quality of MOOCs, including the long-term learning and work performance gains that employees accrue from taking them, would increase employers’ use of MOOCs not just in professional development but also in recruiting and hiring.